2015
DOI: 10.1111/ijac.12394
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of La and Nd Co‐Doped Bismuth Titanate Ferroelectric Ceramics

Abstract: La and Nd co-doped bismuth titanate Bi 3 (La x Nd 1Àx )Ti 3 O 12 (x = 0.4, 0.5, and 0.6) [BLNT] samples were prepared by solid-state reaction method. XRD pattern of calcined powder of BLNT ceramics indicates a single phase of bismuth-layered perovskite structure with no visible impurity phase. The sintered BLNT ceramics showed a uniform microstructure having spherical type grain. Dielectric constant was increased by co-doping due to increase in lattice distortion. Dielectric loss, AC conductance, and leakage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Thus, the polarization of Ti 4+ is improved, then the dielectric constant increases sharply [ 54 , 55 ]. This increase of ε′ r with increasing Bi is also found by S. Islam et al [ 56 ], for Bi-substituted BaTiO 3 ceramics, but the values of ε′ r they obtained are larger than our values. This difference is caused by the substitution of BaTiO 3 by Fe in the Ti site which has the effect of decreasing ε′ r [ 37 ].…”
Section: Resultssupporting
confidence: 84%
“…Thus, the polarization of Ti 4+ is improved, then the dielectric constant increases sharply [ 54 , 55 ]. This increase of ε′ r with increasing Bi is also found by S. Islam et al [ 56 ], for Bi-substituted BaTiO 3 ceramics, but the values of ε′ r they obtained are larger than our values. This difference is caused by the substitution of BaTiO 3 by Fe in the Ti site which has the effect of decreasing ε′ r [ 37 ].…”
Section: Resultssupporting
confidence: 84%
“…So far, it is also a more commonly used method for the preparation of photocatalysts. Islam et al 270 synthesized bismuth titanate nanomaterials by molten salt method and doped with La and Nd to further improve its photocatalytic activity. Molten salt method is widely used and has high synthesis efficiency, which is favored by many researchers.…”
Section: Preparation Processmentioning
confidence: 99%
“…However, BIT suffers from the high coercive force, high dielectric loss, and not enough high remnant polarization [20]. Several types of research have been carried out to improve the performance of BIT by doping or co-doping with suitable rare earth elements such as La, Nd, Mn, etc., in both Bi-site and Ti-site [21][22][23][24]. Islam, et al [23] reported that La and Nd doping and codoping in BIT possess higher performance in the high dielectric constant and low dielectric loss.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of research have been carried out to improve the performance of BIT by doping or co-doping with suitable rare earth elements such as La, Nd, Mn, etc., in both Bi-site and Ti-site [21][22][23][24]. Islam, et al [23] reported that La and Nd doping and codoping in BIT possess higher performance in the high dielectric constant and low dielectric loss. The authors mentioned that the remnant polarization and dielectric constant increase due to the rise of structural distortion and lack of center of symmetry of the bismuth titanate octahedral.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation